Cross-border public transport: Continued barriers despite the EU - Beate Caesar; Michael Heilmann; Jörg Saalbach; Werner Schreiner (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
This paper addresses the extension of cross-border transport within the EU. Despite the longstanding efforts of transport and cohesion policies to improve cross-border transport, many border regions still face challenges related to transport infrastructure and local public transport; these are discussed in the first part of this paper. Transport policy goals and instruments on the EU level are then discussed and their impact is assessed using case studies in the border area. As EU policy and funding instruments are not particularly concrete or binding, there are still significant variations between the national policies of member states. Implementation requires strong political will and secure funding. As transport is an important foundation for other aspects of cross-border cooperation, sustained investment in this key area is required.
urn:nbn:de:0156-40971356; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Cross-border transport; EU policy; cohesion policy; transport policy; trans-European transport networks; European territorial cooperation